Impact of exercise-induced muscle damage on performance test outcomes in elite female basketball players - Doma, K.; Leicht, A.; Sinclair, W.; Schumann, M.; Damas, F.; Burt, D.; Woods, C. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was 2-fold: first, to examine the impact of exercise-induced muscle damage (EIMD) on physical fitness qualities after a basketball-specific training session; second, to determine the reproducibility of the sport-specific performance measures in elite female basketball players. Ten elite female basketball players (age 25.6 ± 4.5 years; height 1.8 ± 0.7 m; and body mass 76.7 ± 8.3 kg) undertook a 90-minute training session involving repeated jumping, sprinting, and game-simulated training. Indirect muscle damage markers (i.e., countermovement jump, delayed onset of muscle soreness [DOMS], and creatine kinase [CK]) and sport-specific performances (i.e., change-of-direction [COD] test and suicide test [ST]) were measured before and 24 hours after training. These measures were also collected 1 week after training to determine the reproducibility of the basketball-specific performance measures. A significant reduction in lower-body power (-3.5 ± 3.6%; p = 0.05), while a significant increase in DOMS (46.7 ± 26.3%; p = 0.05) and CK (57.6 ± 23.1%; p = 0.05) was observed 24 hours after exercise. The ST was also significantly increased (2.1 ± 1.8%; p = 0.05), although no difference was observed for COD (0.1 ± 2.0%; p > 0.05). The intraclass correlation coefficient and coefficient of variation for the COD and ST were 0.81 and 0.90, respectively, and 1.9 and 1.5%, respectively. In conclusion, appropriate recovery should be considered the day after basketball-specific training sessions in elite basketball players. Furthermore, this study showed the usability of performance measures to detect changes during periods of EIMD, with acceptable reproducibility and minimal measurement error.